Hepatitis B, C, and delta in the general population in Mayotte: hepatitis B as a major public health concern - Cécile Brouard; Fanny Parenton; Hassani Youssouf; Stéphane Chevaliez; Emmanuel Gordien; Maxime Jean; Mathias Bruyand; Sophie Vaux; Florence Lot; Marc Ruello; Unono Wa Maore group (BMC Infectious Diseases, 2022)
Abstract Background Located in southwestern Indian Ocean, Mayotte is a French territory, with a very specific demographic, social and health context. To date, epidemiological data on infections by hepatitis B (HBV), C (HCV), and delta (HDV) viruses in Mayotte have been sparse. We aimed to estimate, in the 15–69-year-old general population living in Mayotte, the prevalence of infections by hepatitis B (HBV), C (HCV), and delta (HDV) viruses and the distribution of HBV status: current infection with positive HBs antigen (Ag); resolved infection with positive HBc antibodies and negative HBsAg; immunisation by vaccination with only positive HBs antibodies; and no infection/no immunisation with negative markers. We also described the characteristics of infected people and assessed the determinants of lifetime HBV infection. Methods The Unono Wa Maore survey, implemented in a random sample of the general population in 2018–2019, consisted of an at-home collection of epidemiological data and venous blood samples. Detection of hepatitis B, C, and delta serological and molecular markers was performed. Results Among 5207 eligible people, 4643 responded to the questionnaire (89.2%), with 2917 being tested for HBV and HCV (62.8%). Estimated HBV status was as follows: current infection 3.0% (95% confidence interval [CI]: 2.3–3.9%) (n = 76); resolved infection 27.8% (95% CI: 25.8–29.9); immunisation by vaccination 27.7% (95% CI: 25.9–29.7); and no infection/no immunisation 41.5% (95% CI: 39.3–43.7). One participant was positive for HDV antibodies (Ab) (0.65%) with a negative HDV-RNA viral load. The risk of lifetime HBV infection was higher in men (adjusted prevalence ratio (aPR): 1.55, 95% CI: 1.29–1.89); in people aged 30–49 years (aPR: 3.83, 95% CI: 1.49–9.81) or 50–69 years (aPR: 4.52, 95% CI: 1.77–11.53) compared to those under 20; in individuals who reported no condom use during their first sexual intercourse (aPR: 1.46, 95% CI: 1.01–2.14); and in those living in Dembeni-Mamoudzou (aPR: 1.40, 95% CI: 1.09–1.80) compared to the West-Centre of Mayotte. Finally, six individuals were positive for HCV antibodies (0.21%), including three positive for HCV RNA. Conclusions Mayotte is an area of intermediate endemicity for HBV and low endemicity for HCV and HDV. With a prevalence of HBsAg 10 times higher than in mainland France, a high proportion of people susceptible to HBV infection, and a demographic, health, and social context that may favour its transmission, hepatitis B is a major public health concern in Mayotte.